Designs on success : capturing the blueprint for achievement (Caribbean Export Christ ChurchBB, 2011)
Showcases a broad range of handmade quality designs and innovative products from the Caribbean region. Aims to connect artists to buyers and design enthusiasts from the Caribbean region, North America and Europe.
Keywords: ARTS